Disease Characteristics of Fungal Infection With Nasal Polyps (NP) The Influencing Factors, And Existing Condition Of Rhinosinusitis Among Patients; A Cross-Sectional Study - Khan, Rahmatullah; Sajjad, Waseem; Iqbal, Johar; Idrees, Muhammad (Journal of Rawalpindi Medical College, 2026)
Objective: To determine the frequency of fungal infection among patients, as well as its characteristics and features, in patients with nasal polyps presenting at tertiary care hospitals. Methods: A Cross-Sectional Study was conducted for 6 months after the project's approval, from September 18, 2023, to March 18, 2024. After setting the inclusion criteria, patients were enrolled, and informed written consent was obtained after explaining the study's aims, benefits, and risks. Demographic details, including age, gender, and address, were recorded, and participants underwent physical and medical assessments. Those diagnosed with nasal polyps were tested for fungal infections through histopathology, using biopsy specimens to identify fungal growth, hyphae, and branching patterns. All observations were documented on pre-defined proformas. Results: out of 195 patients, the mean age was 42.30 ± 11.05 years. Participants were distributed across age groups as follows: 10.3% (18-30 years), 36.4% (31-40 years), 30.3% (41-50 years), and 23.1% (>50 years). Of the total, 41.5% were male, 58.5% were female, 66.7% were employed, and 33.3% were unemployed. Most had unilateral (55.4%) rather than bilateral (44.6%) nasal polyps. Fungal infection was present in 45.6% of patients. The mean weight, height, and BMI were 38.66 kg, 1.437 meters, and 18.43, respectively. Stratification by age, gender, employment status, polyp type, and BMI revealed no significant associations with fungal infection, as indicated by p-values above 0.05 in all categories. Conclusion: Patients showed a high frequency of fungal infection after nasal polyps Keywords: Body Mass Index, Fungal Sinusitis, Nasal Polyps.